Borderline personality disorder in adolescence - Kaess, Michael; Brunner, Romuald; Chanen, Andrew M. (Pediatrics, 2014)
Borderline personality disorder (BPD) is a common and severe mental disorder that is associated with severe functional impairment and a high suicide rate. BPD is usually associated with other psychiatric and personality disorders, high burden on families and carers, continuing resource utilization, and high treatment costs. BPD has been a controversial diagnosis in adolescents, but this is no longer justified. Recent evidence demonstrates that BPD is as reliable and valid among adolescents as it is in adults and that adolescents with BPD can benefit from early intervention. Consequently, adolescent BPD is now recognized in psychiatric classification systems and in national treatment guidelines. This review aims to inform practitioners in the field of adolescent health about the nature of BPD in adolescence and the benefits of early detection and intervention. BPD diagnosis and treatment should be considered part of routine practice in adolescent mental health to improve these individuals’ well-being and long-term prognosis.
Gesehen am 21.07.2020